2019
DOI: 10.1038/s41419-018-1271-9
|View full text |Cite
|
Sign up to set email alerts
|

Succinylation-dependent mitochondrial translocation of PKM2 promotes cell survival in response to nutritional stress

Abstract: Tumor growth and progression is characteristically associated with the synergistic effects of uncontrolled cellular proliferation and cell survival under stress. Pyruvate kinase M2 (PKM2) contributes to both of these effects. However, the specific mechanism by which PKM2 promotes uncontrolled proliferation or cell survival under stress in different nutritional environments is unclear. We show that succinylation mediated mitochondrial translocation of PKM2 under glucose starvation plays a role in switching the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 47 publications
1
55
0
Order By: Relevance
“…Interestingly, TLR2 enhances autophagy [46]. Importantly, PKM2 promotes cell survival [47] and regulates STAT3 [48]. In addition, miR-625-5p/PKM2 regulates glycolysis state [49].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, TLR2 enhances autophagy [46]. Importantly, PKM2 promotes cell survival [47] and regulates STAT3 [48]. In addition, miR-625-5p/PKM2 regulates glycolysis state [49].…”
Section: Discussionmentioning
confidence: 99%
“…Pyruvate kinase muscle isozyme 2 (PKM2), which catalyzes the last step of glycolysis to dephosphorylate phosphoenolpyruvate to pyruvate, has been identified as a target of SIRT5 [82,83]. It has been shown that succinylation of PKM2 increases its enzymatic activity.…”
Section: Sirt5 In Mitochondrial Function and Redox Homeostasismentioning
confidence: 99%
“…Inhibition of SIRT5 or substitution of succinylated mimetic mutation (K498E) on PKM2 could increase cell death in response to oxidative stress [82]. In contrast, another group observed that SIRT5-mediated desuccinylation of PMK2 impairs its translocation to mitochondria and stabilization of voltage-dependent anion channel 3 (VDAC3), which led to the opening of mPTP and apoptosis under glucose deprivation [83]. The discrepancy from the above two studies may be resulted from different stress conditions (oxidative stress vs. nutrient stress), cell types (lung cancer cells vs. colon cancer cells) or localization of PKM2 (cytosol vs. mitochondria).…”
Section: Sirt5 In Mitochondrial Function and Redox Homeostasismentioning
confidence: 99%
“…In addition to phosphorylation and O’GlcNAcylation, which regulates the activity of PKM2, PKM2 can also be modified by other post-translational modifications, including acetylation [28], succinylation [29] and methylation [30]. For instance, under normal glucose conditions, deacetylated hnRNP A1 reduced PKM2 in HCC cells and increased PKM1 alternative splicing, resulting in decreased metabolic activity of PK [31].…”
Section: The Function and Regulation Of Pkm2mentioning
confidence: 99%